Thematized Integrated Task for English Conversation Class Setting - Indah Fajaria (Bandar Lampung University (UBL), 2013)
This study aims to demonstrate and explain how to set the English conversation class setting by concerning on the thematized integrated task. In English conversation class, the students are asked to practice their english skillز through many ways; the language focus, the role play, the presentation, and the writing in order to formulate the passage they should explain for their presentation. The research gain some results that show how the thematized integrated task could give more comprehensive understanding toward the topic discussed and covering some English skills.